2020
DOI: 10.18805/ijar.b-3884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kisspeptin on in vitro Maturation of Buffalo Oocytes

Abstract: To explore the effect of kisspeptin on in vitro maturation of buffalo oocytes under different hormonal combinations. For the present study, Kp@10 µg/ml was selected as optimum by assessing the proportion of Cumulus Cell Expansion (CCE) and extrusion of 1st polar body (PB) from the earlier study conducted. Media containing TCM 199 (supplemented with Gentamicin) and oocytes were used as control. Overall, oocytes were allowed to mature in 12 different maturation media viz., Control (T1), Kp at 10 µg/ml (T2), FSH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…In cattle, the addition of KISS1 during IVC and IVF increased the proportion of blastocysts relative to gonadotropins [ 198 ]. Similar beneficial effects of KISS1 on IVF oocyte maturation and developmental competence have been reported in buffalo [ 199 ] and pigs [ 132 , 200 ]. The addition of KISS1 to cultured pig COCs improved oocyte maturation and increased the blastocyst formation rate [ 132 ].…”
Section: Application Of Kiss1 In Assisted Reproduction In Livestocksupporting
confidence: 76%
“…In cattle, the addition of KISS1 during IVC and IVF increased the proportion of blastocysts relative to gonadotropins [ 198 ]. Similar beneficial effects of KISS1 on IVF oocyte maturation and developmental competence have been reported in buffalo [ 199 ] and pigs [ 132 , 200 ]. The addition of KISS1 to cultured pig COCs improved oocyte maturation and increased the blastocyst formation rate [ 132 ].…”
Section: Application Of Kiss1 In Assisted Reproduction In Livestocksupporting
confidence: 76%
“…The Kp effect on buffalo oocyte maturation was first reported in India and standardized concentration with 10 µg/ml and achieved optimum oocyte maturation (73.21%), increasing concentration decreased the maturation (68.77%). In the case of first polar body extrusion also Kp was positively correlated (Rajesh et al, 2018) [29] . The Kp has autocrine action and local interaction with hormones and modulates the FSH, LH, and E2 receptors on oocytes.…”
Section: Buffalomentioning
confidence: 99%
“…Supplementation of the IVM media with gonadotropins and estradiol has been found to be essential for acquisition of developmental capacity of oocytes in cattle (Brackett et al 1989). Supplementation of the IVM media (Rajesh et al 2020) with FCS (Totey et al 1993) or estrus cow serum (Madan et al 1994), follicular fluid (Das et al 1996) has also been found to be necessary for achieving high maturation rates for cattle and buffalo oocytes. Supplementing the culture media with growth factors stimulated embryo development beyond the 8-cell stage (Thibodeaux et al 1993;Yang et al 1993;Borah and Biswas, 2020).…”
Section: Introductionmentioning
confidence: 99%